Perawatan Tahunan Panel Distribusi TM P50 Pada Sistem Jaringan Listrik PT.X - Tuasuun, Minggus; Akhiriyanto, Novan (Politeknik Negeri Malang, 2024)
The electrical network system is the process of distributing electrical energy from power plants to end-users through distribution networks and substations. The distribution network's primary function is to reduce high-voltage electricity, typically from 150 kV to 20 kV, while substations further lower it to a low voltage of 220 VAC for consumer use. However, over time, supporting equipment such as panels, cables, and transformers in the electrical network system can experience a decrease in quality, with a potential decline of up to 20% over 10 years. This degradation is due to various factors, necessitating the installation of protective measures and routine or annual maintenance to prevent potential risks. To maintain equipment quality, maintenance activities include cleaning, testing protection devices, and coordination between substations and workers. These measures are essential for the efficient operation and the successful distribution of electricity. This study evaluates the reliability of equipment at substation panel P50, with test results indicating insulation resistance values of 64,500 MΩ, 73,600 MΩ, and 87,100 MΩ, as well as a delta time of 0.7 ms. The test results indicate that the equipment's reliability is still classified as good, in compliance with the Puil 2000 and IEC 62271-100 standards.